Design of reinforced ground embankments used for rockfall protection - Ronco, C.; Oggeri, C.; Peila, D. (Natural hazards and earth system sciences, 2009)
The prediction of the effects of rockfall on passive protection structures, such as reinforced ground embankments, is a very complex task and, for this reason, both full-scale tests and numerical dynamic modelling are essential. A systematic set of numerical FEM models, developed in the dynamic field, has been implemented in this work to evaluate the conditions of an embankment that has been subjected to the impact of rock blocks of various sizes at different speeds. These analyses have permitted design charts to be obtained. Furthermore, a simplified analytical approach, based on an equilibrium analysis, has been proposed and its results are compared with numerical data in order to assess its feasibility. A good correspondence between the results has been obtained.